2018
DOI: 10.1097/qad.0000000000001752
|View full text |Cite
|
Sign up to set email alerts
|

HIV reservoir dynamics in HAART-treated poor immunological responder patients under IL-7 therapy

Abstract: rhIL-7 treatment initially drives an expansion of HIV reservoir in PIR patients by D28. This expansion is probably not only because of infected cell proliferation, but also to possible enhanced neoinfection, despite highly active antiretroviral therapy. In contrast, subsequent reduction in HIV-DNA load per CD4 T-cell argues for partial elimination of infected cells between D28 and M3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Exogenous administration of IL-7 is associated with dose-dependent increases in CD4 and CD8 T cells in PLWH on ART (143), including HIV-specific CD8 T cells (83). In patients with suppressed HIV, administration of IL-7 led to transient increases in HIV viral load without observed clinical sequelae (84), as well as enhanced anti-HIV CD8 activity. Another T-cell growth factor, IL-15, induces antigen-specific T-cell proliferation, most pronounced in the CD8 compartment (94, 95, 144, 145).…”
Section: Cancer Immunotherapy and Hiv Persistancementioning
confidence: 99%
“…Exogenous administration of IL-7 is associated with dose-dependent increases in CD4 and CD8 T cells in PLWH on ART (143), including HIV-specific CD8 T cells (83). In patients with suppressed HIV, administration of IL-7 led to transient increases in HIV viral load without observed clinical sequelae (84), as well as enhanced anti-HIV CD8 activity. Another T-cell growth factor, IL-15, induces antigen-specific T-cell proliferation, most pronounced in the CD8 compartment (94, 95, 144, 145).…”
Section: Cancer Immunotherapy and Hiv Persistancementioning
confidence: 99%
“…IL-7 signaling plays a central role in T-cell homeostatic proliferation and memory differentiation [23,24,38,[51][52][53]. Recombinant human interleukin 7 (rh-IL-7) has been used in various clinical trials, and has shown favorable effects on immunological recovery in HIV-infected patients [54,55]. Moreover, clinical studies have indicated that rh-IL-7 therapy could enhance the survival and proliferation of both naïve and memory T cells [56][57][58][59], reconstitute T-cell populations in gutassociated lymphoid tissue [60], increase the number of circulat-ing HIV-specific CD8 + T cells [61], and promote the functional recovery of antigen specific-memory T-cell responses [62].…”
Section: Discussionmentioning
confidence: 99%
“…This may explain observations that disulfiram was inefficient to reduce the size of HIV-1 reservoir in a single-arm pilot study [ 53 ] as well as bryostatin not affecting the transcription of latent HIV-1 in a double-blind phase I pilot clinical-trial [ 54 ]. IL-7 use was even associated with transient expansion of HIV-1 reservoir in two independent studies [ 55 , 56 ]. However, it is important to highlight that modulating more genes does not necessarily translate to more efficiency in reservoir reactivation either; indeed it could lead to generalized toxicity or activation of the immune system due to activation of several “off-target” genes [ 44 ].…”
Section: Discussionmentioning
confidence: 99%